Perioperative Challenges in Airway and Ventilatory Management of a Neurosurgical Patient with Klippel–Feil Syndrome - Lakshminarasimhaiah, Geetha; Niranjan, Akshita; Shivakumar, Sonika (Journal of Neuroanaesthesiology and Critical Care, 2024)
Klippel–Feil syndrome, a rare congenital anomaly, has a classical triad of low posterior hairline, short neck, and restriction of neck movements. Complex airway anatomy increases the risk of neurological damage while handling the airway during positioning and laryngoscopy. We address the possible anesthetic challenges that one might face in these patients, such as difficult airway, difficult weaning from the ventilator with increased chances of reintubation, prolonged intensive care and mechanical ventilation, and difficult tracheostomy. Every anesthesiologist must be aware of the available options in the management of a difficult airway in emergent circumstances. Despite the numerous encounters, we were able to effectively manage a case of Klippel–Feil syndrome perioperatively.
Keywords: Klippel–Feil syndrome; airway management; tracheostomy; intracranial hemorrhages